Deciphering the Critical Success Factors of Application Development to Accelerate Digital Transformation and Service Innovation Local Bank Perspectives - Apriansyah Pagua, Jeri; Raharjo, Teguh; Trisnawaty, Ni Wayan (AI Society & STMIK Indonesia, 2025)
The rapid advancement of Industry 4.0 forces local banks to accelerate digital transformation and service innovation. However, Bank ABC faces a low project success rate of only 30%. This study identifies the Critical Success Factors (CSFs) that influence application development projects in local banks using the Analytical Hierarchy Process (AHP). Eight IT Subject Matter Experts (SMEs) from Bank ABC provided expert judgment, and the analysis was conducted using R Studio. The findings highlight five dominant CSFs: leadership, project team commitment, user support, project scale, and regulatory policies. These factors are crucial in improving project success rates, optimizing decision-making, and supporting local banks’ digital transformation. This study contributes to academic research and practical implementation by providing a structured framework for evaluating and prioritizing CSFs in banking application development projects.